Integrasi Islam dan Politik dalam Perspektif Hamka - Amril Amril; Endrika Widdia Putri; Delavia Andrea (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2023)
The human desire to engage in politics is an integral part of their nature. However, in order to conduct politics well and in line with desired goals, a strong understanding of politics is required. Therefore, it is important to understand the concept of politics in Islam through modernist figures such as Hamka, who created a new conception of Islam and politics. The purpose of this research is to analyze Hamka's views on the rules of politics in Islam and the goals of Islamic politics. This research is the result of a qualitative literature study using Hamka's work entitled